Waste cigarette filter as nanofibrous membranes for on-demand immiscible oil/water mixtures and emulsions separation - Liu, Weimin; Cui, Mengke; Shen, Yongqian; Zhu, Guorong; Luo, Lan; Li, Mouji; Li, Jian (Journal of colloid and interface science, 2019)
The cigarette filter coated stainless steel meshes could be applied to on-demand separation of immiscible oil/water mixtures and emulsions with high efficiency. [Display omitted] The rapid industrial growth and the frequent oil spill accidents have led to the large production of oily wastewater. Thus, it is urging to develop a low-cost and eco-friendly material to purify the oily wastewater. In our work, the waste cigarette filter as the raw material was used to prepare cigarette filter coated meshes (CFCMs) by a facile electrospinning approach. The as-prepared CFCMs prewetted with water or oil achieved the special wetting performance of underwater superoleophobicity or underoil superhydrophobicity without any further chemical modification. Hence, the cigarette filter coated meshes with larger or smaller pore size can be applied to on-demand immiscible oil/water mixtures (light or heavy oil/water mixtures) and oil/water emulsions separation (water-in-oil or oil-in-water emulsions), respectively. Moreover, the CFCMs still exhibited high separation efficiency larger than 99.9% for immiscible oil/water mixtures and emulsions after many cyclic testing. The work provides an application in oil/water separation for waste cigarette filters and contributes to reduce the pollution for environment from the waste cigarette filters.